Effects of hauling speed and hook type on the survival of Nemipterids caught by handlines. - Balisco, Rodulf Anthony Tamayo (University of the Philippines Visayas, 2011)
Nemipterids (Nemipteridae) are marine demersal fish that are hard to capture alive and no live samples have been taken or observed in the laboratory or in cgaes. The study was conducted to determine if hauling speed and hook type affect the survival of nemipterids. Hardline was used to catch the target species and fish were observed for short-term survival (1-h). Significant differences were observed on the survival of nemipterids at speeds 120 cm/sec (60%), 60 cm/sec (84%), 30 cm/sec (96%), and 15 cm/sec (98%). High percentage of fish for all treatments experienced barotrauma. There was no differences in survival of nemipterids caught with J-Hook and Circle hooks. It was noted that barotrauma played on important role in the mortality of nemipterids. This study concluded that hauling speed affects the survival of nemipterids but not hook types.